(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2023)
In the competitive landscape of the luxury market, maintaining and enhancing brand value is paramount for sustainable success. This study explores the role of Customer Relationship Management (CRM) in bolstering brand value and influencing purchase intention within the luxury sector, with a focus on the Indian market. Through a comprehensive analysis of CRM practices and their impact on customer perceptions, preferences, and behaviors, this research sheds light on the intricate relationship between CRM, brand value, and purchase intention in the luxury industry. Utilizing both qualitative and quantitative methodologies, including surveys and regression analysis, the study examines how CRM strategies contribute to brand differentiation, customer satisfaction, and loyalty in the luxury segment. The findings underscore the significance of personalized customer interactions, social value, quality, and pricing strategies in shaping brand perceptions and driving purchase decisions. By elucidating the mechanisms through which CRM enhances brand value and purchase intention, this study provides valuable insights for luxury marketers and industry practitioners seeking to optimize their customer engagement strategies and cultivate enduring relationships with affluent consumers.